(untitled) (Research, Society and Development, 2022)
The objective of the present work was to elaborate on a chemically defined extender, based on Tris-casein, and to evaluate its efficacy in the goat semen cryopreservation. For this purpose, three goats were used. Eight ejaculates were collected per male (n = 24). After semen collection, the ejaculates were frozen in a conventional extender (Tris-egg yolk) – control group, as well as an extender based on Tris-casein, in different concentrations (CAS1: 0.125 g/l; CAS2: 0.25 g/l; CAS3: 0.5 g/l), combined with 5% of glycerol. After dilution, 200 x 106 sperm/ml was frozen in an automated system and stored in liquid nitrogen (−196 ºC). After thawing (37 ºC, 30 s), the samples were submitted to kinetic analysis (CASA) and functional analysis, through plasma membrane integrity, acrosome integrity and mitochondrial membrane potential. Regarding the kinetic parameters, plasma membrane integrity, acrosome integrity and mitochondrial membrane potential, there were no significant differences (P > 0.05) between the groups evaluated, with the exception of flagellar beat cross frequency (BCF), where the CAS3 group had a higher value (P ≤ 0.05) than the control group. It can be concluded that the chemically defined extender based on Tris-casein presents a viable alternative to the conventional diluent used for freezing goat semen.